2018
DOI: 10.1155/2018/6152020
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Magnetic Properties of Ba3[Cu0.8−xZnxMn0.2]2Fe24O41 Z‐Type Hexaferrites

Abstract: We report on the synthesis and characterization of Ba3[Cu0.8−xZnxMn0.2]2Fe24O41 (x = 0.0, 0.2, 0.4, 0.6, and 0.8) barium hexaferrites. The samples were prepared by high-energy ball-milling technique and double-sintering approach. The effects of Zn substitution for Cu on the structural and magnetic properties of the prepared samples were investigated using X-ray diffraction (XRD), scanning electron microscopy (SEM), and vibrating sample magnetometer (VSM). XRD patterns of the samples revealed the presence of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…It was reported that the incorporation of divalent metal ions such as Cu 2+ , Zn 2+ , Ca 2+ , Ni 2+ , and Mn 2+ in Z-type hexaferrite may improve their properties [12,20,[22][23][24][25][26]. In a recent study, the effects of the substitution level of Zn 2+ on the purity and magnetic properties of Ba 3 (Cu 0.8−x Zn x Mn 0.2 ) 2 Fe 24 O 41 hexaferrite were investigated [27]. In this study, it was demonstrated that intermediate levels of Zn substitution for Cu (0.2 ≤ x ≤ 0.6) was suitable for the production of a highly pure Z-type phase, with increased saturation magnetization, and reduced coercivity and magnetocrystalline anisotropy.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the incorporation of divalent metal ions such as Cu 2+ , Zn 2+ , Ca 2+ , Ni 2+ , and Mn 2+ in Z-type hexaferrite may improve their properties [12,20,[22][23][24][25][26]. In a recent study, the effects of the substitution level of Zn 2+ on the purity and magnetic properties of Ba 3 (Cu 0.8−x Zn x Mn 0.2 ) 2 Fe 24 O 41 hexaferrite were investigated [27]. In this study, it was demonstrated that intermediate levels of Zn substitution for Cu (0.2 ≤ x ≤ 0.6) was suitable for the production of a highly pure Z-type phase, with increased saturation magnetization, and reduced coercivity and magnetocrystalline anisotropy.…”
Section: Introductionmentioning
confidence: 99%